The Effect of Yoga Exercise on Blood Sugar Levels In Type II Diabetes Mellitus Patients in Karangasem Village, Surakarta - Rusila, Jihan; Widiyono, Widiyono; Sutrisno, Sutrisno (Student Scientific Journal, 2023)
Background:Diabetes mellitus (DM) is a chronic disease in which the pancreas is unable to produce enough insulin or when the body cannot effectively use the insulin it produces, causing an increase in the concentration of glucose in the blood (hyperglycemia). Management of DM can be carried out in pharmacological and non-pharmacological ways for DM patients, one of the non-pharmacological measures for DM is yoga.Objective:In general, this study aims to determine the effect of yoga exercise on blood sugar levels in type II DM patients in Karangsem Village, Surakarta.Method:Types of research Quasi Experimentsby using a planpre and post test without control. The research sample was 23 respondents with techniques purposive sampling. The instruments in this study used yoga practice SOPs and GCU toolsEasy Touch to measure blood sugar levels before and after doing yoga exercises. Data analysis usingUji Paired t-test. Research result:The average blood sugar level before doing yoga is 148.609 and the average blood sugar level after doing yoga is 127.870. There is an effect of yoga exercise on blood sugar levels (p value = 0,001< 0,05). Conclusion:There is a significant effect on blood sugar levels in type II DM patients in Karangasem Village, Surakarta.